2005
DOI: 10.1097/00129804-200505000-00005
|View full text |Cite
|
Sign up to set email alerts
|

A Theory-based Intervention to Improve Nursesʼ Knowledge, Self-efficacy, and Skills to Reduce PICC Occlusion

Abstract: The peripherally inserted central catheter (PICC) is an effective intermediate and long-term central vascular access device. Its functions are comparable with those of other percutaneously placed central venous catheters. However, its high occlusion rate and the consequent infection risk may disrupt therapy for patients. The primary investigator in this study developed an educational intervention based on Albert Bandura's social learning theory, and hypothesized that increasing nurses' knowledge and self-effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 23 publications
3
29
0
Order By: Relevance
“…The presence of a CVADs team with dedicated doctors and nurses which follow standardized procedures for the overall management of PICCs, from the insertion to weekly monitoring and follow-up, could have contributed to this finding [19,20]. In conclusion, PICCs are a safe and feasible alternative option to other CVADs in the clinical management of patients with hematologic malignancies undergoing intensive and prolonged treatments.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of a CVADs team with dedicated doctors and nurses which follow standardized procedures for the overall management of PICCs, from the insertion to weekly monitoring and follow-up, could have contributed to this finding [19,20]. In conclusion, PICCs are a safe and feasible alternative option to other CVADs in the clinical management of patients with hematologic malignancies undergoing intensive and prolonged treatments.…”
Section: Discussionmentioning
confidence: 95%
“…Our result was in accordance with the previous study, which has identified that a significant decrease in the catheter occlusion rate is associated with the increase of expertise of nurses and self-efficacy related to the care of PICCs. [22] So far, no clear evidence in the literature of complication rates in the course of insertion was found. Results presented in this study demonstrated that the intervention started at the insertion period decreased the rate of unplanned extubations dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…They found that an overall increase in nurses' knowledge and self-efficacy related to PICC care led to a significant reduction in the catheter occlusion rate, from 29% to 8.5%, over a 6-month period. 17 Lehoux and associates 18 used a conceptual framework to determine why and how patients use health technology at home. In both of these studies, the theory or framework helped guide the research and had an impact on the study design and conduct of the study.…”
Section: The Literature Searchmentioning
confidence: 99%